Barriers to change in family businesses - Jose Daniel Lorenzo-Gomez (European Journal of Family Business (EJFB), 2020)
A series of characteristics affects the willingness of a family business to change and renew. Both change and renewal are necessary to maintain the continuity of the company in the long term in order for it to be handed down to the following generation. Approaches to the identification of barriers to change that are specific to the characteristics of family businesses are analyzed with the aim of identifying factors that potentially have the great - est impact on the decision-making and implementation of change processes. These factors include the generation at the head of the family business; the influence of interest groups, particularly the duality between the company and the family; and the greater or lesser par- ticipation of professionals from outside the family.
Keywords: M19; 650; Strategic change; barriers to change; family business